Analisis Sifat Kandungan Kimia Dan Penggunaan Material Lokal Kinang Jingkion Sebagai Agregat Kasar Terhadap Karakteristik Campuran Laston (AC) WC Di Kabupaten Yalimo - Herman Ferdinand Putera Safanpo; Bahtiar Bahtiar; Yohanes B. J. Rusmanta; Harmonis Rante; Apolo Safanpo; Janviter Manalu (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the nature of chemical content, analyze abrasion value and optimum asphalt content using local Kinang Jingkion as road pavement material. In this study, XRF and XRD testing methods were used to determine the chemical content of Kinang Jingkion local material, then testing the characteristics of rough aggregate to determine the abrasion value, testing fine aggregate characteristics, and testing asphalt pen 60/70 and marshall test to determine the optimum asphalt content (KAO). The tests obtained the results of comparative data analysis between laboratory tests and literature standards that meet the eligibility requirements. The results showed that: First, the results of XRF and XRD analysis on Wilihingke samples, 0.15 mm granules, 2.36 mm granules, and Kinang Holuwon found that all chemical elements contained in the four samples were solid metal inorganic chemical elements. The results of this analysis prove that the four samples, which are fine aggregates and coarse aggregates, do not contain organic substances. Where the results of this analysis are by the requirements of aggregates which are one of the components in the concrete mixture, where the aggregates used must meet certain conditions, one of which must not contain excess organic matter because it can undergo decay by bacteria using dissolved oxygen; Second, from the test results obtained, the aggregate wear value (abrasion) was 32.69%; Third, based on the test results, the value of the Marshall parameter with Optimum Asphalt Content (KAO) obtained a value of 6.125%.